Pengaruh Green Product, Green price, Green Place dan Green Promotion terhadap Purchase Intention Konsumen di Pasar Induk Among Tani Kota Batu - Rully Sabrina; Rois Arifin; Abdullah Syakur Novianto (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to examine the effects of green product, green price, green place, and green promotion on consumers’ purchase intention at Pasar Induk Among Tani, Batu City. A quantitative approach with a survey method was employed, involving 142 respondents selected through purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that green product, green price, and green place have a positive and significant effect on purchase intention when tested partially, while green promotion does not have a significant partial effect. However, the simultaneous test shows that all green marketing mix variables collectively have a significant influence on consumers’ purchase intention. These findings highlight the importance of an integrated green marketing strategy in enhancing consumers’ purchase intention. Keywords: Green Product, Green Price, Green Place, Green Promotion, Purchase Intention